Estimation of stature from Arm span-An anthropometric study on adult Bangladeshi women - Khan, Khushruba Rahman; Akter , Farhana; Huq, Md Razaul; Rahman, Mushfika; Banik, Shyamal Chandra; Naushaba, Humaira (Journal of Dhaka National Medical College & Hospital, 2021)
Background: Upper limb is the most movable part and main working tools of human body. Anthropometry is used in identification of individuals, criminals and a person in accidental death like fire, ship & air accidents, etc. and prevention of impersonation in Forensic criminology. Objectives: To measure the individuals stature, arm span and assess the relationship between them. Methods: This is descriptive and analytical type of study which was carried out in the department Anatomy, Sir Salimullah Medical College, Dhaka from July 2010 to December 2011. The ethical permission was taken from Institutional Ethics Committee (IEC) of SSMC. The number of subject was 100 right handed adult Bangladeshi women belonging to age group of 25 to 45 years. Arm span along with stature were measured directly from the subjects by direct physical method. The data were then statistically analyzed by computation to find out its normative value. Regression analysis was done to see the correlation between stature and this variable. Result: Arm span showed significant positive correlation with the stature. Conclusion: Stature estimation is an important tool in various departmental sciences. J. Dhaka National Med. Coll. Hos. 2021; 27 (02): 15-18